2018
DOI: 10.3390/atmos9060233
|View full text |Cite
|
Sign up to set email alerts
|

Snow Level Characteristics and Impacts of a Spring Typhoon-Originating Atmospheric River in the Sierra Nevada, USA

Abstract: Abstract:On 5-7 April 2018, a landfalling atmospheric river resulted in widespread heavy precipitation in the Sierra Nevada of California and Nevada. Observed snow levels during this event were among the highest snow levels recorded since observations began in 2002 and exceeded 2.75 km for 31 h in the northern Sierra Nevada and 3.75 km for 12 h in the southern Sierra Nevada. The anomalously high snow levels and over 80 mm of precipitation caused flooding, debris flows, and wet snow avalanches in the upper elev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Some AR tracks with tropical origins in the far West Pacific first travel westward-in the opposite direction of the prevailing midlatitude westerly winds-before eventually recurving toward the northeast (example track highlighted in Figure 3a). This behavior is strongly suggestive of ARs resulting directly or indirectly from the remnants of West Pacific tropical cyclones (e.g., Cordeira et al, 2013;Hatchett, 2018).…”
Section: Comparison Of Ar Versus Background Temperature Trends 331mentioning
confidence: 94%
See 1 more Smart Citation
“…Some AR tracks with tropical origins in the far West Pacific first travel westward-in the opposite direction of the prevailing midlatitude westerly winds-before eventually recurving toward the northeast (example track highlighted in Figure 3a). This behavior is strongly suggestive of ARs resulting directly or indirectly from the remnants of West Pacific tropical cyclones (e.g., Cordeira et al, 2013;Hatchett, 2018).…”
Section: Comparison Of Ar Versus Background Temperature Trends 331mentioning
confidence: 94%
“…Second, surface air temperatures during AR events exert considerable influence on snow accumulation totals (Guan et al, 2010), with warm air temperatures associated with higher snowlines (Dettinger, 2011). Third, elevated AR temperatures are especially characteristic of exceptionally warm and moist Pineapple Express-type ARs, the tropical origins of which tend to increase the potential for adverse hydrological impacts in regions with substantial winter snowpack (Guan et al, 2016;Hatchett et al, 2018). Long-term warming of ARs could thus increase the snowline elevation, decrease snow accumulation, and decrease the probability that an individual AR will bring snow.…”
Section: Introductionmentioning
confidence: 99%
“…Because of downstream dependence on snow-derived water resources and susceptibility to flooding from snowmelt events, California is an ideal location for examining the changes in historical precipitation partitioning. Studies have found evidence for changes in California's cryosphere consistent with a warming climate, including an upslope shift in winter snow line elevation (Hatchett et al, 2017), delayed early season snowpack accumulation (Hatchett and Eisen, 2019), earlier peak snow water equivalent (Kapnick and Hall, 2010), and…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan is located in the Pacific Ocean and has a subtropical climate, and it is frequently impacted by typhoons. Increasing sea surface temperatures can effectively increase the surface latent heat flux during the typhoon season, which means that the heavy precipitation and strong convective flow of a typhoon can induce a region of extreme negative OLR anomalies (Liebmann and Smith, 1996;Lee et al, 2006;Susskind et al, 2012;Hatchett, 2018). The latitude and altitude effects on OLR variations around the study area can be ignored, owing to the narrow latitude range and smooth topography, except in the Central Range of Taiwan.…”
Section: Methodsmentioning
confidence: 99%